Friedrich Engels and Marxian political economy - Hollander, Samuel (Historical perspectives on modern economics., 2011)
"This book rejects the commonly-encountered perception of Engels as perpetuator of a "tragic deception" of Marx, and the equally persistent body of opinion treating him as His Master's Voice. Engels's claim to recognition is reinforced by an exceptional contribution in the 1840s to the very foundations of the Marxian enterprise, a contribution entailing not only the "vision" but some of the building blocks in the working out of that vision. Subsequently, he proved himself to be a sophisticated interpreter of the doctrine of Historical Materialism and an important contributor in his own right"--